4q21.2q21.3 Duplication: Molecular and Neuropsychological Aspects - Iourov, Ivan Y.; Zelenova, Maria A.; Vorsanova, Svetlana G.; Voinova, Victoria V.; Yurov, Yuri B. (Current Genomics, 2018)
During the last decades, a large amount of newly described microduplications and microdeletions associated with intellectual disability (ID) and related neuropsychiatric diseases have been discovered. However, due to natural limitations, a significant part of them has not been the focus of multidisciplinary approaches. Here, we address previously undescribed chromosome 4q21.2q21.3 microduplication for gene prioritization, evaluation of cognitive abilities and estimation of genomic mechanisms for brain dysfunction by molecular cytogenetic (cytogenomic) and gene expression (meta-) analyses as well as for neuropsychological assessment. We showed that duplication at 4q21.2q21.3 is associated with moderate ID, cognitive deficits, developmental delay, language impairment, memory and attention problems, facial dysmorphisms, congenital heart defect and dentinogenesis imperfecta. Gene-expression meta-analysis prioritized the following genes: ENOPH1, AFF1, DSPP, SPARCL1, and SPP1. Furthermore, genotype/ phenotype correlations allowed the attribution of each gene gain to each phenotypic feature. Neuropsychological testing showed visual-perceptual and fine motor skill deficits, reduced attention span, deficits of the nominative function and problems in processing both visual and aural information. Finally, emerging approaches including molecular cytogenetic, bioinformatic (genome/ epigenome meta-analysis) and neuropsychological methods are concluded to be required for comprehensive neurological, genetic and neuropsychological descriptions of new genomic rearrangements/ diseases associated with ID.
Keywords: Genomic variations